Richard den Anden og Hamlets spejl - Tessing Schneider, Magnus (Peripeti, 2025)
In Shakespeare’s Hamlet (1601), the title hero commissions an acting company to perform a play before Claudius, which recalls the murder of his father, but Claudius instead perceives the play as a threat to his life. The article analyses this episode as the dramatization of a real performance of Shakespeare’s Richard II, which took place on 7 February 1601.